Good Governance and Ethical Value: Are They Sync in Harmony? - Qoshidah, Mukhtasyarah Minhajul; Nurrahmawati, An; Norizan, Saifulrizan Bin (Universitas Ahmad Dahlan, 2025)
This study aims to provide empirical evidence on the impact of good corporate governance, reflected in managerial ownership, audit quality, board size, independent board size, and board gender diversity, on corporate ethical value disclosure. The research focuses on mining sector companies listed on the Indonesia Stock Exchange from 2017 to 2022, using a sample of 56 companies and 315 observations selected through purposive sampling. Applying multiple regression analysis on panel data, the findings highlight that audit quality, board size, and board gender diversity positively influence corporate ethical value disclosure, whereas managerial ownership and independent board size do not significantly impact. The novelty of this research lies in its application of the corporate ethical value index, comprising 40 items across 10 categories, and the utilization of five principles of good corporate governance. The study underscores the importance of implementing good corporate governance, particularly through audit quality, board size, and gender diversity, to enhance corporate ethical value disclosure. These practices can improve company transparency, strengthen stakeholder trust and reputation, and promote a more moral and accountable business environment. This study contributes to the literature by bridging the gap between governance structures and ethical disclosures in a developing market context, offering a comprehensive empirical model that integrates diverse governance indicators with a detailed ethical value index rarely used in previous research.